Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00284-015-0961-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpes Virus 1 Major Immediate Early Transcription Unit 1 (IETU-1) Uses Alternative Promoters to Transcribe BICP0 and BICP4 Transcripts

Abstract: Immediate early (IE) genes are transcribed immediately after infection in BHV1 from two different immediate early transcription units. It is reported that the immediate early transcription unit I (IE TU1) of Bovine herpesvirus 1 (BHV1) transcribes two proteins BICP0 and BICP4 from a single promoter by alternative splicing but with identical 5'UTR. We found that the transcripts of BICP0 and BICP4 have different 5'UTRs. The bioinformatics analysis shows two similar spatially arranged TATA less promoter for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are reports showing that C/EBPα can transactivate IE genes of BoHV-1 25 , 37 39 , in vitro and also that bTIF can activate promoters that lack OCT-1 motifs provided an alternate mechanism for DNA binding is available 10 . We recently reanalyzed the promoters of known IE gene of BoHV-1 9 and observed that instead of two 4 , 5 , 40 , there are three IE transcription units and each of the transcription units have similarly placed INR, DPE and OCT-1 motifs thus reinforcing the hypothesis of OCT-1 having a role in the transactivation of IE genes in BoHV-1.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There are reports showing that C/EBPα can transactivate IE genes of BoHV-1 25 , 37 39 , in vitro and also that bTIF can activate promoters that lack OCT-1 motifs provided an alternate mechanism for DNA binding is available 10 . We recently reanalyzed the promoters of known IE gene of BoHV-1 9 and observed that instead of two 4 , 5 , 40 , there are three IE transcription units and each of the transcription units have similarly placed INR, DPE and OCT-1 motifs thus reinforcing the hypothesis of OCT-1 having a role in the transactivation of IE genes in BoHV-1.…”
Section: Discussionmentioning
confidence: 82%
“…2A–C ) suggesting one TSS for each gene. The BICP0, BICP4 and BICP22 also have one transcription start site 9 . The distance between TSS and putative translation start site (ATG) varied among these three genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation